2015
DOI: 10.1177/1524839915609059
|View full text |Cite
|
Sign up to set email alerts
|

A Male Promotores Network for Latinos

Abstract: Background. Lay health advisor (LHA) interventions with Latino men are rare, especially in emerging Latino communities. We present a process evaluation of a male LHA network aiming at connecting Latino men to various kinds of services and to the Latino community. It assesses the feasibility of (1) maintaining a steering coalition; (2) hiring, training, and retaining male LHA; and (3) recruiting and assisting underserved participants. Methods. Project management data and LHA debriefings were analyzed qualitativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…A third limitation is that most participants were women, which is often the case in CHW interventions ( 25 ). Reaching men, particularly Hispanic men, is a challenge to address; using male CHWs could help ( 26 ). A fourth limitation is that the rates of those who used the voucher and needed a particular service provide a conservative estimate of program ability to help people acquire needed services.…”
Section: Discussionmentioning
confidence: 99%
“…A third limitation is that most participants were women, which is often the case in CHW interventions ( 25 ). Reaching men, particularly Hispanic men, is a challenge to address; using male CHWs could help ( 26 ). A fourth limitation is that the rates of those who used the voucher and needed a particular service provide a conservative estimate of program ability to help people acquire needed services.…”
Section: Discussionmentioning
confidence: 99%
“…The specific intervention components were drawn from: a) the research team’s previous studies with preschool children (25, 45, 46, 56) and promotores (19, 35), b) published Latino child obesity prevention interventions (6, 10, 14, 52, 57, 59), and c) formative research conducted in Phase 1 of the study. Guidance and suggestions to improve the intervention protocol were received through feedback from: (a) the Community Research Advisory Board (CRAB) through the Center for Health Equity at the University of Pittsburgh, (b) Latino Engagement Group for Salud (LEGS), a coalition of community members, researchers and health and social service providers, and (c) a Research Advisory Board consisting of 5 faculty experts on family-based interventions and Latino health research from the University of South Carolina.…”
Section: Methodsmentioning
confidence: 99%
“…One study reported how participatory approaches allowed for the modification of the research programme throughout conception, development, and implementation. 30 Multiple publications provided evidence on how iterative feedback from stakeholder during the studies could aid partnerships, improving the recruitment of individuals to implement or take part in the intervention, 17,18,23,28,38,47 and dissemination. 23 One study also highlighted that partnerships were a feasible and appropriate means to support intervention implementation, 20 whilst one set of authors reported that partnerships with non-academics can ultimately strengthen research.…”
Section: Benefits Of Participatory Approaches To Researchmentioning
confidence: 99%